Leadership Styles, Communications, and Resources Affecting The Development of E-Budgeting In The Public Sector - Tri Artharini Nungki Noor Susanti Oktaviani; Cris Kuntadi (Dinasti International Journal of Education Management And Social Science, 2022)
Prior research or relevant research is crucial to any scientific or research article. When prior research or relevant research has been conducted in these areas, it strengthens the theory and phenomena of the relationship or influence between variables. The method used in this article is a literature review which is a review of various articles related to the implementation of e-budgeting. This article examines the leadership style, communication, and resources that influence the implementation of e-budgeting in the public sector, as well as a literature review on State Financial Management. The purpose of this article is to develop a working hypothesis regarding the relationship between variables for use in future research. 1) Leadership style affects the implementation of e-budgeting in the public sector; 2) communication influences the implementation of e-budgeting in the public sector; and 3) resources affect the implementation of e-budgeting in the public sector.